Allenoate prenucleophiles: a triply diastereoselective approach to beta-hydroxy esters containing all-carbon alpha-quaternary centers - Maki, Samantha L.; Maity, Pradip; Dougherty, Shannon; Johns, Jennifer; Lepore, Salvatore D. (Organic Letters, 2019)
Allenyl esters activated by titanium(IV) underwent additions to a wide range of aldehydes in high regio- and diastereoselectivities leading to products containing an all carbon quaternary center bearing an alpha-vinyl group that was installed with high selectivity for the Z-geometry. An aldol product was also converted to an indanone offering a new route to this important compound class. Product triple diastereoselectivity has been rationalized using a concerted transition-state model.